PERSEPSI SISWA MENGIKUTI MATA PELAJARAN BAHASA JEPANG DENGAN MODEL STUDENT CENTERED LEARNING DI KELAS XI IPS 2 SMA NEGERI 9 PEKANBARU - Ismail, Millentio Festkine; Basri, Merri Silvia; Widiati, Sri Wahyuni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research is a quantitative descriptive study which aims todetermine students' perceptions of taking Japanese language lessons using the StudentCentered Learning model. Independent learning strategies by class of 2022 studentswhen learning hiragana letters. The population and sample in this research were classXI IPS 2 students, totaling 32 students. The instrument used in this research was aquestionnaire consisting of 20 statements. Based on the results of the analysis carriedout on questionnaires and assisted by interviews with several students, it was found thatthe students' perceptions of taking Japanese language lessons using the SCL modelwere positive which can be seen from the results of the questionnaire, namely that 12students had very positive perceptions with a percentage of 43.75%, as many as 18Other students had a positive perception with a percentage of 56.25%, and there wereno students who had less positive or negative responses. Apart from that, internalfactors which include interest and attention also had positive results based on students'perceptions, while for external factors there were 3 students who gave less positiveresponses for reasons that were acceptable and needed to be paid attention to in thefuture.Key Words: Student Perceptions, Student Centered Learning, Japanese